"What do we do with our lives?" Conversations About Work and Conversations at Work - Labrecque, Lisandre (Revista Internacional de Organizaciones, 2019)
Everyday conversations reveal the great normative preoccupations of societies, both in their themes and in their modalities. The world of work is one of the main worlds of conversation we have studied: we talk about work and we talk at work. Contemporary individuals seek to singularize themselves through work and in conversations about work: it becomes a statutory and an aesthetic experience insofar as it resonates with a way of life and a broader experience of reality.